Organization of replication of ribosomal DNA in Saccharomyces cerevisiae. - Linskens, M H (1988)
Using recently developed replicon mapping techniques, we have analyzed the replication of the ribosomal DNA in Saccharomyces cerevisiae. The results show that (i) the functional origin of replication colocalizes with an autonomously replicating sequence element previously mapped to the nontranscribed spacer region, (ii) only a fraction of the potential origins are utilized in a single S phase, and (iii) the replication forks moving counter to the direction of transcription of the 37S precursor RNA stop at or near the termination site of transcription. Consequently, most ribosomal DNA is replicated unidirectionally by forks moving in the direction of transcription and most replicons are larger than the repeat unit. The significance of this finding for the replication of abundantly transcribed genes is discussed.